Jihad Penista Agama Jihad NKRI: Antonio Gramsci's Hegemony Theory Analysis of Radical Da'wah Phenomena in Online Media - Fatmawati, Fatmawati; Noorhayati, Siti Mahmudah; Minangsih, Kalsum (Al-Albab, 2018)
This article explores the new trends of Islamic radicalism through missionary jihad against a blasphemer (Ahok) as part of the jihad for the NKRI (Unitary State of the Republic of Indonesia). The trend of radical dakwah in online media is interesting to research, regardless of the interest of the local election, or Caliphate and NKRI sharia on the other hand. The purpose of this research is to find out the trend of radical dakwah in online media by calling jihad against a blasphemer as part of the NKRI jihad and its implication. The questions in this study will be examined using the theory of domination of interests (hegemony), given the position of the radicals is to seize the hegemony of society through online viral media. In conclusion, the use of the term Jihad against a blasphemer, and political branding that radical groups still maintain the integrity of the NKRI is a hegemonic form to defeat the cultural power of the moderate, tolerant, and plural Muslims. These radicals, together with the intellectual actors behind them, realize that in order to gain legitimacy of religious power, they must collaborate with the MUI (fatwa institution), then use social media to invite all to participate to do counter discourse. After that, they collaborated with politicians to advocate the idea they propose. Finally, they use symbolic Islamic slogans to bring Muslims to the struggle that they do.